Influences of Physalis peruviana L. and Lupinus albus L. fruits extracts on the levels of some biochemical parameters in brain and muscle tissues of type II diabetic rats - Kirecci, Oguz Ayhan; Erman, Fazilet; Ozsahin, Ayse Dilek; Erman, Orhan; Kaya, Tubay; Yilmaz, Okkes (Mattioli 1885, 2018)
New functional foods are increasingly sought to improve the treatment of diseases related to glucose and lipid metabolism. The present study was designed to investigate the possible antidiabetic and antioxidant effects of goldenberry and lupin on brain and muscle tissues of streptozotocin-induced type II diabetic rats. Type II diabetes was produced in albino rats by the streptozotocin injection. Wistar albino rats were divided into four groups, each one containing 10 rats: non-diabetic control group, STZ-type II Diabetes group, STZ-type II Diabetes+goldenberry group, and STZ-type II Diabetes+lupin group. After one week from the injection, goldenberry and lupin were injected to rats for 2 months. Malondialdehyde, glutathione, cholesterol, and fatty acid levels, which are signs of lipid peroxidation, were measured in brain and muscle tissues. In type II diabetes, malondialdehyde increased compared to the control group. Glutathione decreased in the both tissues and all of the streptozotocin-induced diabetic groups. In type II diabetes, brain cholesterol levels decreased. Treatment with similar doses of goldenberry and lupin significantly reduced oxidative stress, augments antioxidant system and altered fatty acid metabolism in these tissues, thereby maintaining favourable fatty acid distribution affected by diabetic complications. These results validate the use of goldenberry and lupin fruits as a treatment against diabetes mellitus and its complications and suggest it is suitable to continue studies for its safe therapeutic use.
Keywords: diabetes mellitus; goldenberry; lupin; malondialdehyde; glutathione; brain; muscle